O uso das TIC na promoção da acessibilidade de estudantes disléxicos na UFSM - Bastos, Liziane Forner (2018)
This dissertation is linked to the research line Development of Educational Technologies in Network, of the Post-Graduate Program in Educational Network Technologies - PPGTER, Professional Master's, Federal University of Santa Maria - UFSM. The objective of the study was to understand how the use of information and communication technologies enhances access, permanence and completion in higher education of students with dyslexia. As a result, the Master's product consists of an E-book containing Guidelines for Accessibility of Students with Dyslexia in Higher Education, intended for teachers and other professionals of the institution. The theoretical reference brings information related to Accessibility in Higher Education; Dyslexia and its particularities and The evolution of ICT and its implications in the inclusion process. According to the methodology, it is proposed an applied, qualitative research and has as its method the case study. The semi structured interview was adopted as a data collection instrument in this study, which had as target audience, dyslexic students enrolled in the UFSM, besides these, the undergraduate students in which these students are enrolled and the professionals of the multidisciplinary team of the Coordination of Educational Actions - CAED involved in these cases. Content analysis was used to interpret the data. To this end, four categories of analysis were listed, namely: Political Issues and ICT; Institutional Issues and ICT, Pedagogical Issues and ICT and Social Issues and ICT. The results show that despite the movements in search of accessibility actions in the UFSM, it is still imperative to implement new measures in view of the fragility of the inclusion process in the university, among them the need for greater investment in ICT as a possibility to facilitate learning, the participation and the autonomy of the students. However, in addition to the question of the use of ICT as a means of accessibility, it was possible to identify many other aspects that should be reflected in the university field and could not go unnoticed in the analysis.